Cosplay sebagai Representasi Budaya Pop Jepang di Medan - waode anggi anggraini waode; irwan (WIDAI Japanese Journal, 2023)
This study aims to analyze cosplay as a representation of Japanese pop culture in Medan City. Using a descriptive qualitative method, data were collected through observation, interviews, and documentation involving local cosplayer communities. The results show that cosplay in Medan is not merely a form of entertainment but also a medium of self-expression, creativity, and identity formation among young people. This phenomenon reflects the process of glocalization — a blend of Japanese culture with local Indonesian values. Therefore, cosplay serves as a cultural interaction medium that enriches the dynamics of popular culture in Medan and strengthens the role of youth in the development of global culture at the local level.